2018
DOI: 10.1042/cs20171525
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone, SGK1, and ion channels in the kidney

Abstract: Hyperaldosteronism, a common cause of hypertension, is strongly connected to Na+, K+, and Mg2+ dysregulation. Owing to its steroidal structure, aldosterone is an active transcriptional modifier when bound to the mineralocorticoid receptor (MR) in cells expressing the enzyme 11β-hydroxysteroid dehydrogenase 2, such as those comprising the aldosterone-sensitive distal nephron (ASDN). One such up-regulated protein, the ubiquitous serum and glucocorticoid regulated kinase 1 (SGK1), has the capacity to modulate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 120 publications
1
43
0
3
Order By: Relevance
“…These processes occurred via genomic signalling cascades, related to mineralocorticoid receptors. They also reported that eplerenone, a mineralocorticoid receptor blocker, inhibited the TRPM7 current [4]. On the other hand, Sontia et al [40] showed that aldosterone reduced expression of renal TRPM7 without effecting TRPM6.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These processes occurred via genomic signalling cascades, related to mineralocorticoid receptors. They also reported that eplerenone, a mineralocorticoid receptor blocker, inhibited the TRPM7 current [4]. On the other hand, Sontia et al [40] showed that aldosterone reduced expression of renal TRPM7 without effecting TRPM6.…”
Section: Discussionmentioning
confidence: 98%
“…Non-genomic pathways include mineralocorticoid receptor, EGF receptor, and Gprotein coupled receptor-dependent mechanisms as well as mineralocorticoid receptorindependent actions [35][36][37][38][39]. Valinsky et al [4] showed that aldosterone promotes the plasma membrane expression of TRPM7, and therefore TRPM7 flow. These processes occurred via genomic signalling cascades, related to mineralocorticoid receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ENaC can be regulated by a variety of proteases found in CF sputum [43]. Moreover, the expression level of ENaC and SPLUNC1 can be regulated by a number of hormones and soluble proteins [30,44]. Small molecule inhibitors of ENaC such as amiloride and its derivatives work by reducing Po, but the channels remain on the surface of cells.…”
Section: Discussionmentioning
confidence: 99%
“…Since SGK1 is regulated by a wide variety of signals, it has many functions and is reported to be involved in the regulation of several carriers and ion channels, including the epithelial sodium channel (EnaC), the renal outer medullary K + channel (ROMK), the voltage-gated K + and Na + channel, the Na + /K + 2Cl − cotransporter (NKCC2), the glutamate transporters, etc. [7,8]. One of the mechanisms whereby SGK1 regulates channels is through the phosphorylation of Nedd4 −2 , a ubiquitin ligase that targets channels for degradation.…”
Section: Introductionmentioning
confidence: 99%